EFEK TERAPI OKSIGEN HIPERBARIK TERHADAP JUMLAH NEUTROFIL PADA TIKUS WISTAR MODEL NEFROPATI DIABETIK YANG DIINDUKSI STREPTOZOTOCIN - Noel Eloy Fariyanto Kartosinggih (Surabaya Biomedical Journal, 2025)
Abstract Study aims : Diabetes mellitus is a metabolic disease characterized by an increase in glucose levels in the body which causes various complications, one of which is diabetic nephropathy which is the main cause of chronic failure cases in Indonesia. The purpose of this experimental research is to determine the decrease in the number of neutrophils after hyperbaric therapy in wistar rats in diabetic nephropathy. Method: This research method used a posttest only control group design method which consisted of three sample groups, namely the negative control group, the positive control group, and the treatment group. The negative control group consisted of healthy rats, the positive control group consisted of ND model rats induced with 75 mg/kg streptozotocin, while the treatment group consisted of ND model rats treated with TOHB. In these three groups, IL-1β inflammatory serum and blood were collected on the fourteenth day to determine IL-1β levels and number of neutrophils in each group. Result: There was a significant decrease in number of neutrophils (p<0,001) in the kidneys of Wistar rats of the diabetic nephropathy model after Hyperbaric Oxygen Therapy (HBOT) Conclusion: Hyperbaric oxygen therapy has an effect on the number of neutrophils.